Strategy For Enhancing The Economic Values of Dance Art Based On Creative Industries - Karti, Galih; Wisnu Dermawan; Damar Kasyiyadi; Agustina Ayu Andira (Jurnal Bisnis, Manajemen, dan Akuntansi, 2026)
The negative stigma regarding the low sales value and uncertain career projection has diminished the image of dance art as a profession in Indonesia. Because of this phenomenon, a comprehensive strategy is required to increase the sales value of creative industry-based dance art. The objective of this research is to identify the standard quality and the strategy to increase sales value through multi-perspectives examination: artists, education, organizers, and audiences. Implementing the descriptive-qualitative approach, the data was collected through semi-structured interviews and observation on informants who are actively involved in the dance art ecosystem. The result of this research shows that the increase in sales value depends on the balance between the artistic idealism and market demand, supported by managerial skill and professionalism. In conclusion, dance art requires an integrated system based on innovation, professionalism, discipline, and business skills. The roles of the government and academics are extremely crucial in formulating policies that address the issues of fee standardization and strategic promotion. Therefore, dance art can be a competitive profession that is sustainable economically.